A study on customers’ perception towards the information counter, MunLoong-Hankyu Jaya Bangsar, Kuala Lumpur / Rohaya Ishak - Ishak, Rohaya (1998)
The objective of this thesis was to identify the level of customers' perceptions of service quality on customer service provided by the company. The study approach was a research study of the Information Counter of MunLoong- Hankyu Jaya, Bangsar (MHJB), Kuala Lumpur. Information on the level of perceptions among the MHJB customers was gathered. However, in the process of delivering good customer service, the counter is facing a lot of implementation problem and issues that seems to hinder the achievement of giving high quality of service. The study findings show that the current level of customers' perceptions is not encouraging enough as the service quality determinants which is reliability, responsiveness, assurance and empathy are having negative perceptions. However, the tangible determinant is having positive perception. Other than that they also have good personality, as they are rated as courteous, having sincere interest in solving customer problems, willing to help customers and dress neatly.